(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to identify the principles and methods employed in the application of compliance auditing by the oversight and audit departments in Islamic banks, and to study and analyze the extent of adherence by the sample Islamic banks to compliance auditing requirements and its impact on earnings management practices. To achieve the research objective, the analytical descriptive approach was adopted to describe and analyze the data obtained from the sample banks in order to verify the hypotheses. The deductive approach was employed in the theoretical part of the research, while the analytical descriptive approach was used to describe, process, and analyze the data from the sample banks to assess the validity of the hypotheses. The research reached several conclusions, the most important of which are: all values of the (t) statistic were significant at a level of less than (0.05), indicating a statistically significant relationship between compliance auditing with work ethics standards and earnings management in the three banks. Additionally, from the analysis of the results, the regression coefficients of the independent variables were positive, meaning that an increase of one unit in the independent variable leads to an equivalent increase in the dependent variable. The research recommends that banks should implement more transparent earnings management strategies based on sound foundations, with a focus on reducing unwarranted fluctuations in earnings, thereby enhancing the credibility of financial statements and increasing investor confidence. Moreover, banks should consider improving their business models to strengthen these relationships, which can lead to overall improvement in financial performance.